A novel homozygous RIPK4 variant in a family with severe Bartsocas‐Papas syndrome. Issue 6 (13th March 2021) - Dinçer, Tuba; Gümüş, Evren; Toraman, Bayram; Er, İdris; Yildiz, Gokhan; Yüksel, Zafer; Kalay, Ersan
Abstract: Bartsocas‐Papas syndrome (BPS) is a rare autosomal recessive disorder characterized by popliteal pterygia, syndactyly, ankyloblepharon, filiform bands between the jaws, cleft lip and palate, and genital malformations. Most of the BPS cases reported to date are fatal either in the prenatal or neonatal period. Causative genetic defects of BPS were mapped on the RIPK4 gene encoding receptor‐interacting serine/threonine kinase 4, which is critical for epidermal differentiation and development. RIPK4 variants are associated with a wide range of clinical features ranging from milder ectodermal dysplasia to severe BPS. Here, we evaluated a consanguineous Turkish family, who had two pregnancies with severe multiple malformations compatible with BPS phenotype. In order to identify the underlying genetic defect, direct sequencing of the coding region and exon‐intron boundaries of RIPK4 was carried out. A homozygous transversion (c.481G>C) that leads to the substitution of a conserved aspartic acid to histidine (p.Asp161His) in the kinase domain of the protein was detected. Pathogenicity predictions, molecular modeling, and cell‐based functional assays showed that Asp161 residue is required for the kinase activity of the protein, which indicates that the identified variant is responsible for the severe BPS phenotype in the family.